Japanese nurse practitioners' legal liability ambiguity regarding their medical practice: a qualitative study - Shoko Sugiyama; Kyoko Asakura; Nozomu Takada (BMC, 2020)
Abstract Background Nurse practitioners' role is always expanding. The Japanese Nurse Practitioner (JNP) system was initiated in 2015 to shift some aspects of doctors' work to various other healthcare professionals, including nurses. JNPs' fulfillment of their roles was shown to have a certain degree of efficacy and provide positive outcomes for patients (e.g., shortening hospitalization period). Nurse practitioners are considered legally liable for their medical practices because they are performed on doctors' behalf; however, in real life, there is ambiguity regarding such practice. It is necessary to clarify nurse practitioners' legal liability in order to ensure the safety of their medical practice and protect them in medical procedures performed on physicians' behalf. This study aimed to clarify how JNPs understand their own legal liability in medical practice. Methods A qualitative, inductive research design was adopted to record participants' opinions. The survey was conducted from October 2017 to February 2018. Participants were nurses working as JNPs at general hospitals in eastern Japan. We recruited participants via snowball sampling. Results With regard to JNPs' legal liability in their medical practice, three themes understanding were observed: "determining whether the JNP has the ability to perform the assigned medical procedure," "exercising caution when performing medical procedures on a doctor's behalf" and "an urge to follow up with appropriate medical practice until the end of care." Conclusions We demonstrated that JNPs recognized their own legal liability in medical practice. They had to protect themselves because their legal position was ambiguous. Furthermore, JNPs accepted that diagnosis and drug prescription could be performed on behalf of doctors if trusting relationships had been previously established.